Schistosoma mansoni FES Tyrosine Kinase Involvement in the Mammalian Schistosomiasis Outcome and Miracidia Infection Capability in Biomphalaria glabrata - Tavares, Naiara Clemente; Gava, Sandra Grossi; Torres, Gabriella Parreiras; de Paiva, Clara Ênia Soares; Moreira, Bernardo Pereira; Lunkes, Felipe Miguel Nery; Montresor, Langia Colli; Caldeira, Roberta Lima; Mourão, Marina Moraes (Frontiers in Microbiology, 2020)
Schistosomiasis is a neglected tropical disease (NTD) caused by helminthes from the Schistosoma genus. This NTD can cause systemic symptoms induced by the deposition of parasite eggs in the host liver, promoting severe complications. Functional studies to increase knowledge about parasite biology are required for the identification of new drug targets, because the treatment is solely based on praziquantel administration, a drug in which the mechanism of action is still unknown. Protein kinases are important for cellular adaptation and maintenance of many organisms homeostasis and, thus, are considered good drug targets for many pathologies. Accordingly, those proteins are also important for Schistosoma mansoni, as the parasite relies on specific environmental signals to develop into its different stages. However, the specific roles of protein kinases in S. mansoni biology are not well understood. This work aims at investigating the tyrosine-protein kinase FES (Feline Sarcoma) functions in the maintenance of S. mansoni life cycle, especially in the establishment of mammalian and invertebrate hosts’ infection. In this regard, the verification of Smfes expression among S. mansoni stages showed that Smfes is more expressed in infective free-living stages: miracidia and cercariae. Schistosomula exposed to SmFES-dsRNA in vitro presented a reduction in movement and size and increased mortality. Mice infected with Smfes-knocked-down schistosomula exhibited a striking reduction in the area of liver granuloma and an increased rate of immature eggs in the intestine. Female adult worms recovered from mice presented a reduced size and changes in the ovary and vitellarium; and males exhibited damage in the gynecophoral canal. Subsequently, miracidia hatched from eggs exposed to SmFES-dsRNA presented changes in its capability to infect and to sense the snail mucus. In addition, the SmFES RNAi effect was stable from miracidia to cercariae. The establishment of infection with those cercariae reproduced the same alterations observed for the knocked-down schistosomula infection. Our findings show that SmFES tyrosine kinase (1) is important in schistosomula development and survival; (2) has a role in adult worms pairing and, consequently, female maturation; (3) might be essential for egg antigen expression, thus responsible for inducing granuloma formation and immunomodulation; and (4) is essential for miracidia infection capability. In addition, this is the first time that a gene is kept knocked down during three different S. mansoni life stages and that a tyrosine kinase is implicated in the parasite reproduction and infection establishment in the mammalian host. Accordingly, SmFES should be explored as an alternative to support schistosomiasis treatment and morbidity control.